A different view on sodium balance - Titze, Jens (Current Opinion in Nephrology and Hypertension, 2015)
Textbook theory holds that extracellular fluids readily equilibrate, electrolyte concentrations in the extracellular fluid compartments are constant, and the kidney is solely responsible for controlling the body sodium content.Investigation of salt and water balance traditionally relies on short-term studies of bodily responses to extremes in salt intake. Ultra-long-term sodium balance studies instead studied the kidney's response to constant salt intake. The studies suggest that steady-state sodium balance in humans is characterized by storage and release of sodium from the body. The absence of accompanying changes in the body fluid matrix indicates the presence of metabolically relevant sodium reservoir sites in the body. In rats and mice, sodium is stored in skeletal muscle and skin. Homeostatic immune cells control reservoir electrolyte metabolism via the lymphatics. Failure of this extrarenal clearance process results in skin electrolyte accumulation and arterial hypertension. Noninvasive detection of sodium reservoir metabolism in patients by NaMRi methodology allows rapid transfer into the clinical arena.Body sodium content in humans and animals is not constant, does not always readily equilibrate with water, and is not exclusively controlled by the kidneys. This different view provides with new research avenues for basic and clinical investigators.
EVALuna2:3755